The challenge of nature and The Permanents in the trinity of character traits, rationality and arts in the thought of Farabi and Ibn Sina - Fataneh TavanaPanah; Ghasem ali kouchnani (اخلاق وحیانی, 2024)
Nature and The Permanent are two important factors in the formation of stable and dominant models in each of the three levels of character, rationality and art in Farabi and Ibn Sina's thought. The Permanents refers to a characteristic in the soul that is difficult or impossible to destroy. Nature and natural talents are among the things that are hardly subject to deterioration and destruction.It is because of this difficulty that both The Permanent and nature are considered in rooting stable behaviors. As much as nature, the permanents plays a role in the three levels of character, rationality and art. Just like nature, The Permanents, are the factor of prevailing behaviors, thoughts and arts and thus the formation of stable and fixed theoretical, emotional and behavioral patterns come from the permanents.The problem of this research refers to the challenge and contradiction of the requirements and rulings of the two classes of nature and the permanents. The explanation is that sometimes there is a contradiction and duality between the natural requirements and the the permanents properties, for example, the nature requires altruism and the properties formed in the soul are the origin of actions against altruism, in such a case, their properties and requirements become substitutes for the nature. This issue can be seen under the title of matching the status of natural, rationality and artificial properties with natural affairs.The Permanent act like nature. The naturalization of education and ethics as well as arts with the help of making them The Permanent is therefore emphasized by Ibn Sina. If the conflict increases and it is revealed, depending on the degree of penetration and institutionalization of the permanents, nature will weaken or disappear completely. In this research, in a descriptive-analytical way, we first point to the place of conflict, i.e. the challenge of nature and the The Permanent, and then we address the issue that in the event of confrontation between the two forces of nature and the the permanents, considering that both of them are the factors of stability and formation. Which of these two forces does the human soul obey?